A method for efficient expression of Pseudomonas aeruginosa alginate lyase in Pichia pastoris. Issue 2 (17th February 2016) - Yue, Michael M.; Gong, Wendy W.; Qiao, Yu; Ding, Hongbiao
ABSTRACT: As an eco-friendly biocatalyst for alginate hydrolysis, bacteria-derived alginate lyase (AlgL) has been widely used in research and industries to produce oligosaccharides. However, the cost of AlgL enzyme production remains high due to the low expression and difficulty in purification from bacterial cells. In this study we report an effective method to overexpress the Pseudomonas aeruginosa AlgL (paAlgL) enzyme in Pichia pastoris . Fused with a secretory peptide, the recombinant paAlgL was expressed extracellularly and purified from the culture supernatant through a simple process. The purified recombinant enzyme is highly specific for alginate sodium with a maximal activity of 2, 440 U/mg. The enzymatic activity remained stable below 45°C and at pH between 4 and 10. The recombinant paAlgL was inhibited by Zn 2+, Cu 2+, and Fe 2+ and promoted by Co 2+ and Ca 2+ . Interestingly, we also found that the recombinant paAlgL significantly enhanced the antimicrobial activity of antibiotics ampicillin and kanamycin against Pseudomonas aeruginosa . Our results introduce a method for efficient AlgL production, the characterization, and a new feature of the recombinant paAlgL as an enhancer of antibiotics against Pseudomonas aeruginosa.